Plane truth : a private investigator's story - Davies, Carl A. (Algora Pub., 2001)
A free-lance sleuth investigating the demise of Pan AM 103 over Lockerbie raises new questions about corporate and tribal loyalties, structural engineering, and money and politics, in a credible scenario that understandably could never be admitted by anyone who might have been involved.